1999
DOI: 10.1002/(sici)1521-4079(199912)34:10<1251::aid-crat1251>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Growth and Properties of Guanidine Doped Triglycine Sulfate Crystal

Abstract: Guanidine doped TGS crystal is grown from the aqueous solution. The pyroelectric properties of GTGS crystal are studied, the result shows that GTGS crystal has better pyroelectric properties than those of pure TGS crystal. The effects of organic dopant on pyroelectric properties of TGS crystal are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 1 publication
1
15
0
Order By: Relevance
“…TGS has a major disadvantage that it is depolarized by thermal, mechanical, and electrical means. In order to overcome this difficulty, several studies have been attempted with different organic and inorganic dopants to achieve effective internal bias to stabilize the domains to increase the pyro electric and ferroelectric properties of TGS crystals [8][9][10][11][12][13][14].In this article, we report the effect of doping TGS crystal with potassium di hydrogen phosphate (KDP), and the characterization studies adopted for the grown crystal.…”
Section: Introductionmentioning
confidence: 99%
“…TGS has a major disadvantage that it is depolarized by thermal, mechanical, and electrical means. In order to overcome this difficulty, several studies have been attempted with different organic and inorganic dopants to achieve effective internal bias to stabilize the domains to increase the pyro electric and ferroelectric properties of TGS crystals [8][9][10][11][12][13][14].In this article, we report the effect of doping TGS crystal with potassium di hydrogen phosphate (KDP), and the characterization studies adopted for the grown crystal.…”
Section: Introductionmentioning
confidence: 99%
“… is dipole moment of O-H··O bond, E is external electric field, V is spin lattice interaction and A k and B k are position and momentum operators, ω k is the harmonic phonon frequency V (3) and V (4) are third and fourth order atomic force constant.…”
Section: Model Hamiltonianmentioning
confidence: 99%
“…Since then many experimental studies on dielectric, ferroelectric, thermal and scattering properties of TGS crystal have been done. Recently Sun et al [3] have done growth and study about pyroelectric properties of pure and doped TGS crystal. Arago and Gonzalo [4] have done hysteresis curve studies of TGS crystal.…”
Section: Introductionmentioning
confidence: 99%
“…However, the dipole moment is not the only factor for the increase in the pyroelectric properties of TGS crystal. It was reported that thiourea and urea doped into TGS crystal improved the pyroelectric properties of TGS crystal [13,14]. These molecules have larger dipole moments than glycine.…”
Section: Article In Pressmentioning
confidence: 99%